Belajar dari Bungo: mengelola sumberdaya alam di era desentralisasi - Adnan, H.; Tadjudin, D.; Yuliani, L.; Komarudin, Heru; Lopulalan, D.; Siagian, Y.; Munggoro, D. (Center for International Forestry Research, 2008)
Since President Soeharto stepped down, decentralization has offered a better governance system for this nation of more than 220 million people of varied ethnic groups spread over more than 15,000 islands. Despite its potential, implementation of decentralization has been riddled with unexpected problems. Decentralization turned out to have created problems, ranging from conflicts among people who refused regional fragmentation, conflicts between newly-created districts and the original, larger district from which they were created, and between local and central government. Problems with forest and forestry are no exception. Since decentralization took effect in 2001, it has contributed to deforestation. FAO even mentions that annual deforestation has reached about 1,87 million ha. In the midst of the misery of Indonesia’s forestry, many stakeholders strive to build a better forestry system. One group of these lives and works in Bungo district, in the province of Jambi in Sumatra, where committed stakeholders have searched for a better strategy for managing their local natural resources. Since the 1990s, NGOs, universities, international research institutes and others engaged in research and programmes have worked together and accomplished a great deal, including the establishment of multistakeholder processes and the recognition of customary community laws. This book is a collection of research results, lessons and experiences developed by various parties, aiming to fully and comprehensively depict how decentralization has taken place and show the impacts on local livelihoods and natural resource management. The book provides many insightful and valuable experiences and lessons. Learning from Bungo consists of 26 chapters, a foreword by Zulfikar Ahmad, the Head of Bungo District and closing remarks by Erna Rosdiana, the Directorate General of Land Rehabilitation and Social Forestry, Ministry of Forestry. The first part paints a portrait of Bungo district, its abundant natural resources and the changes in forest cover in recent years. The second part presents the importance of local wisdom and knowledge in anticipating new threats and challenges from the external environment. The third part deals with the ecological and economic aspects of local resources. Finally, Part four describes conflicts over natural resources and some thoughts on local adaptation through collaboration and collective action among stakeholders to resolve the problems.